Avaliação da variabilidade genética em progênies de Myracrodruon urundeuva (Fr. All) na Baixada Cuiabana - Almeida, Erica Vitória (2011)
This study aimed to estimate genetic parameters and values for height, diameter, number of leaf flushes and survival of half-sib progenies mastic in a field test in the town of Santo Antonio do Leverger, MT. The test was established as follows: a) the nursery - the design was randomized blocks with 30 treatments (progenies) and six replicates (blocks) and six plants per plot. The same design was used for the field phase. The progeny test was installed in the nursery UFMT in Cuiaba in randomized blocks, with 30 treatments (progenies), 6 replicates (blocks) and 6 plants per plot. At three months old progenies were evaluated for the characters: a) seedling height - in centimeters, b) stem diameter - in millimeters, and c) number of leaf flushes. The variables were analyzed using the method of mixed linear model (univariate additive) obtained through the Selegen REML/BLUP genetic statistical software. The individual narrow sense heritabilities for the traits studied can be considered of moderate magnitude (0.20, 0.16 and 0.15) for height, diameter and number of leaf flushes, respectively. The individual genetic variation coefficients of (CVgi%) considered expressive (9.05%, 9.11% and 11.95%). The selective accuracy was (0.81, 0.77 and 0.76) for height, diameter and number of foliar shoots. At two years old, the progenies were evaluated for the characters: a) height (cm) b) Diameter (mm), c) number of foliar shoots and, d) survival. The genetic parameters were obtained through the Selegen REML/BLUP genetic statistical software. The heritability estimates of individual coefficients (0,05, 0,02 0,10 and 0,02) for height, diameter, number of leaf flushes and survival, respectively, values that are considered of low magnitude. The genetic gains with individual selection ranged from 8 to 14 cm tall for the character, from 0,49 to 0,78 mm in diameter, 4 to 8 for leaf number of launches. The predicted values can maximize the chances of genetic progress by selection. The results of genetic heritability associated with individual and average families, encourage the continuation of the breeding program of mastic in the marshland of Cuiabá in view the possibility of increased gene expression of genetic material in the sequence of field assessments.